THE EFFECT OF REGIONAL ORIGINAL INCOME AND BALANCED FUNDS ON REGIONAL EXPENDITURES IN EAST KALIMANTAN PROVINCE - Achmad Adri Rahim; Noor Ellyawati; Vitria Puri Rahayu (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Government with openness has become a demand in Indonesia. This has led to increased demands for transparency and accountability. These two aspects become very important in the management of government, including in the field of regional financial management and regional financial management, this itself cannot be separated from what is called Regional Original Revenue, Balancing Funds and Regional Expenditures. This study aims to determine the effect of Regional Original Income and Balancing Funds on Regional Expenditures in East Kalimantan Province. Data collection is carried out at the Central Statistics Agency of East Kalimantan Province in the form of a APBD realization report for 15 periods, namely the 2005-2019 fiscal year. Based on the results of the t test, it shows that the two independent variables are smaller than the significance level, so that there is a partial and significant effect between Regional Original Income and Balancing Funds on Regional Expenditures in East Kalimantan Province. Based on the results of the f test, the sig value of 0.000 <0.05, it can be concluded that the Regional Original Income and the Balancing Fund have a simultaneous and significant effect on regional spending. in East Kalimantan Province.